PEMASARAN SENI PERTUNJUKAN RAKYAT DI INDONESIA MELALUI PLATFORM DIGITAL SENIPEDIA.COM - Novianto, Wahyu; Murtono, Taufik; Hudha, Tafsir (Institut Seni Indoensia Surakarta, 2022)
The rapid pace of technology in the 4.0 era constructs conventional transaction models into digital transactions with the growth of various digital startups. The use of digitalization for folk performing arts is still not maximally accommodated, even though the internet has spread to villages. Although various conceptions and discourses on the digitization of folk performing arts continue to roll out, they are only carried out by academics and only a small part of the performing arts community is able to utilize the internet and gadgets for means of communication and interaction with a wide audience. This study shows the utilization of digital internet technology that has changed the pattern of face to face interaction to screen to face through the digital application Senipedia.com as one of the start-ups engaged in the realm of folk performing arts development in Indonesia. The various benefits of marketing through the Senipedia.com digital application are becoming a meeting place for all groups to form the habit of assessing and being judged virtually, preserving cultural heritage and historical values that are useful in the future, and becoming an archive that can be reused as educational material that contains values of mutual cooperation, a sense of independence, freedom of expression, and the formation of mutual appreciation of folk performing arts through the digital-virtual world.